Silicon And Porous Silicon – Based Extended Gate Field Effect Transistor For pH And Cations Sensor - Kabaa, Emad Adnan Said (2018)
Following the advances in biochemical sensors based on porous silicon (PSi) in the late 20th century, several studies have been carried out to take advantage of the intrinsic properties of PSi for development of biochemical sensors. The commercial ntype silicon (Si) has been used in two forms, namely, flat surface and porous layer based on extended gate field effect transistor (EGFET), as sensors for the pH and cations (Na+, K+, Mg2+, and Ca2+). This study aim is to improve the low silicon sensitivity as a cations sensor by increasing the surface area in a cheap and simple way.